2002
DOI: 10.1163/157181702401475412
|View full text |Cite
|
Sign up to set email alerts
|

Importance and Difficulties of Victim-Based Research in Post-Conflict Societies

Abstract: No Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…For instance, scholars have found that Yazidi survivors of ISIL atrocities in Syria share an ‘understanding of justice principally focused on local issues, immediate concerns, agency, and prospects of a better future’ rather than a ‘narrow’ focus on ‘accountability through criminal trials’ (Akhavan et al, 2020: 2). In their call for localized alternatives, these authors echo lessons from work that emphasizes context-sensitive reparative measures like compensation or land restitution (Robins, 2011; Rombouts, 2002: 217).…”
Section: Introductionmentioning
confidence: 94%
“…For instance, scholars have found that Yazidi survivors of ISIL atrocities in Syria share an ‘understanding of justice principally focused on local issues, immediate concerns, agency, and prospects of a better future’ rather than a ‘narrow’ focus on ‘accountability through criminal trials’ (Akhavan et al, 2020: 2). In their call for localized alternatives, these authors echo lessons from work that emphasizes context-sensitive reparative measures like compensation or land restitution (Robins, 2011; Rombouts, 2002: 217).…”
Section: Introductionmentioning
confidence: 94%